Trouble with zombies: Bare life, Muselmanner and displaced people - Stratton, Jon (Edinburgh University Press, 2011)
This article considers the increase in media representations of zombies during the first decade of the 2000s. It argues that a connection can be read between the new preoccupation with zombies and anxieties over the apparent threat posed by those without rights attempting to enter Western countries. The article sets up a theoretical argument using the work of Giorgio Agamben. Taking on board Agamben's discussion of ‘bare life’, the article follows Agamben in making a link between this idea and the Muselmann, the Jew reduced to the walking dead in the concentration and death camps. For Agamben, bare life is central to the functioning of the modern state. The article suggests that bare life is a way of connecting the Muselmann with the zombie as that monster has been elaborated in films since George Romero's Night of the Living Dead (1968). Indeed, where Agamben argues that the werewolf was the characterising monster of the premodern era, this article argues that the zombie is the characterising monster of the modern era. The article goes on to make the connection between bare life, Muselmänner, zombies and displaced people, most commonly understood as asylum seekers.